2017
DOI: 10.1101/128769
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The rate of transient beta frequency events predicts impaired function across tasks and species

Abstract: Beta frequency oscillations (15-29Hz) are among the most prominent signatures of brain activity. Beta power is predictive of many healthy and abnormal behaviors, including perception, attention and motor action. Recent evidence shows that in non-averaged signals, beta can emerge as transient high-power "events". As such, functionally relevant differences in averaged power across time and trials can reflect accumulated changes in the number, power, duration, and/or frequency span of the events. We show for the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…Consistent with the Engel and Fries ( 17 ) model, Shin et al. ( 22 ) demonstrated that a transient beta burst just prior to a liminal stimulus reduced the probability of stimulus detection. In primates, Lundqvist et al.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Consistent with the Engel and Fries ( 17 ) model, Shin et al. ( 22 ) demonstrated that a transient beta burst just prior to a liminal stimulus reduced the probability of stimulus detection. In primates, Lundqvist et al.…”
mentioning
confidence: 77%
“…The resulting time–frequency spectrograms were filtered with a two-dimensional Gaussian filter (standard deviations: 1 Hz/6 ms), and peaks were identified using image dilatation with a 5-by-5 structuring element consisting of ones with a center value of zero (implementation: Tony Fast; https://gist.github.com/tonyfast/d7f6212f86ee004a4d2b ). Peak values less than 6 times the median power across all time points at the peak frequency were excluded ( 22 ). An example of a burst that exceeded this threshold is shown in Figure 1C .…”
Section: Methodsmentioning
confidence: 99%
“…The tested power thresholds ranged from 0.1 to 20 in 30 equally sized steps. For each simulation the best threshold was determined by calculating the maximum correlation between mean single trial power and the area, represented as a proportion of total TFR area per trial, above the cutoff (Shin et al 2017). Following this, we found local maxima that were above the previously calculated cutoff.…”
Section: Power-threshold Detection Methodsmentioning
confidence: 99%
“…Lastly, we simulated a scenario in which the power difference was caused by a transient burst rate difference; in the HP trials the p event = 0.9 and in the LP trials the p event = 0.1. Our attention centered specifically on the transient burst count, given both its significance in numerous studies (e.g., Shin et al, 2017;Little et al, 2019) and that it indicates the presence of bursts, and thus all other characteristics are dependent on it. Initially, we visualized the single-trial burst count recovered by single-trial power for both scenarios in Fig 4A . The results indicated that as the number of detected bursts increased so did single-trial power, in all scenarios.…”
Section: Figure 3 Comparison Of the Burst Characteristics For Each Si...mentioning
confidence: 99%
“…Oscillations in the beta frequency band have been the focus of numerous studies due to their central role in cortical processing, particularly in mediating top-down commands (Bastos et al, 2015;Engel and Fries, 2010;Michalareas et al, 2016;Richter et al, 2017), for their prominence in the motor system (Baker, 2007;Baker et al, 1997;Klostermann et al, 2007;Sanes and Donoghue, 1993) and during Parkinson's disease (PD) (Cassidy et al, 2002;Kühn et al, 2004;Lalo et al, 2008). Across different experimental conditions, changes in beta band activity have been linked with motor performance (Kühn et al, 2004;Tan et al, 2014), decision-making (Herz et al, 2018), motor-task completion (Feingold et al, 2015), tactile perception (Shin et al, 2017) and PD treatment state (Kühn et al, 2006(Kühn et al, , 2009Little et al, 2013;Tinkhauser et al, 2017aTinkhauser et al, , 2017b.…”
Section: Introductionmentioning
confidence: 99%